2011
DOI: 10.5194/cp-7-151-2011
|View full text |Cite
|
Sign up to set email alerts
|

Can oceanic paleothermometers reconstruct the Atlantic Multidecadal Oscillation?

Abstract: Abstract. Instrumental records of the North Atlantic sea surface temperature reveal a large-scale low frequency mode of variability that has become known as the Atlantic Multidecadal Oscillation (AMO). Proxy and modelling studies have demonstrated the important consequences of the AMO on other components of the climate system both within and outside the Atlantic region. Over longer time scales, the past behavior of the AMO is predominantly constrained by terrestrial proxies and only a limited number of records… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Although uncertainty in our age model (up to 194 years during the early Holocene) also limits our confidence in the higher frequency peaks, it is worth noting that spectral power at the 87‐year period is common in proxies forced by solar variability, possibly reflecting an influence of the Gleissberg solar cycle [ Peristykh and Damon , 2003]. Spectral power at the 60‐year period may reveal a connection between SSS variability in the Florida Straits and the Atlantic Multidecadal Oscillation (AMO) (30–80 year period) [ Dima and Lohmann , 2007], which some modeling studies suggest is the result of high‐frequency AMOC variability during the Holocene [ Delworth and Mann , 2000; Enfield et al , 2001; Heslop and Paul , 2011]. Knight et al [2006] showed that the warm AMO phase is associated with a northward displacement of the ITCZ over the tropical Atlantic, suggesting a possible influence of the AMO on the tropical Atlantic hydrologic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although uncertainty in our age model (up to 194 years during the early Holocene) also limits our confidence in the higher frequency peaks, it is worth noting that spectral power at the 87‐year period is common in proxies forced by solar variability, possibly reflecting an influence of the Gleissberg solar cycle [ Peristykh and Damon , 2003]. Spectral power at the 60‐year period may reveal a connection between SSS variability in the Florida Straits and the Atlantic Multidecadal Oscillation (AMO) (30–80 year period) [ Dima and Lohmann , 2007], which some modeling studies suggest is the result of high‐frequency AMOC variability during the Holocene [ Delworth and Mann , 2000; Enfield et al , 2001; Heslop and Paul , 2011]. Knight et al [2006] showed that the warm AMO phase is associated with a northward displacement of the ITCZ over the tropical Atlantic, suggesting a possible influence of the AMO on the tropical Atlantic hydrologic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic wide anomalous heat fluxes were imposed to create a basin scale temperature dipole that induced changes in northward heat transport (Heslop and Paul 2011). Additionally, idealized freshwater forcing scenarios were employed to reduce the strength of the simulated AMOC in a systematic manner.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the relation between AMOC and sea level discussed below, our approach is based on several factors. First, the high Holocene sedimentation rate (on average decadal resolution or better) makes this record superior to those from tidal marshes and other marine sediment records [ Heslop and Paul , , but see Boessenkool et al , ]. Second, sea level change reconstructed from SST proxies is free from the complicating effects of vertical land motions caused by tectonic, GIA, and other processes.…”
Section: Introductionmentioning
confidence: 99%